Conceptos de probabilidad y estadística en análisis de fallas de componentes mecánicos - Hernández, Héctor (Ingeniería e Investigación, 1996)
When a mechanical component fails, somehow or other, the applied load becomes equal or greater than the fail load. Taking in mind this principle and considering the statistical variability of both, applied stress and strength, the concept of failure probability is cached. Assuming that both strength and stress have a normal distribution, then failure probability increases with: (a) the reduction of the difference between mean value of strength and stress, (b) the increase of strength and stress variance. Defects introduced by manufacturing and defects introduced into service such as voids, pits, inclusions or cracks can increase the failure probability and decrease the reliability. This is due to the' increase in the overlapping between the two distributions, of stress and strength. This depends on failure mode such as plastic collapse, brittle fracture and failure by fatigue. When the failure mode is by slow crack growth, reliability can be improved by using of nondestructive inspection methods to detect subcritical crack sizes.